A Case Study: Role of Darvyadi Lauha in Pandu Roga - sharma, Dr. Ammana; Singh, Dr. O.P; Shukla, Dr. Shweta Gyanendra (RA Journal of Applied Research, 2022)
Ayurvedic classics have always attempted to meet the requirement for knowledge breakthroughs in order to keep up with the demands of time. The stated goal of Ayurveda as a medical system is to help humanity live a healthier and longer life. Pandu or Anemia, is one of the most common illnesses that people face. Pandu is a disorder that causes pale discoloration of the body. Pandu Roga is a disease that is described in Ayurveda's main classical texts. Pandu Roga is a Rasa pradoshaja vikara, according to Acharya Charak. Pandu Roga was given a name according on how it was presented. The symptoms of pandu roga are similar to anemia. Anemia is a disease which is characterized by decreased hemoglobin concentration. Because Anemia is such a widespread ailment in today's culture, and the adverse effects of allopathic iron preparations, like constipation and gastrointestinal irritation, are so common, a healthier alternative, named Darvyadi Lauha, is required. Triphala, Trikatu, Daruhaldi, Vidanga and Lauhabhasama are the ingredients. These herbs function on the levels of Dosha, Dushya, Agni, and Strotas, while Lauha Bhasma has Rakta Dhatu Vardhan property.